PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKAMELALUI PENERAPAN TEORI BRUNER BERBANTUAN MEDIA KUBUS SATUAN - Rosmiati, Rosmiati; Bistari, Bistari; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstracThis research aim of the study was to find out about the activities and results of learning mathematics using Bruner's Theory assisted by media unit cubes in the class V of Darit State Islamic Middle School. The method used is descriptive method. Collaborative nature. The research subjects were teachers who taught Mathematics and the fifth grade students of Darit State Madrasah Ibtidaiyah. Settings for setting settings in class. The technique used is the direct observation technique. While the data collection tool is the observation sheet. The data collected is data about the activities of teachers and students and the learning outcomes of students in the learning process. The results of the study in the first cycle of the activities of students in mathematics learning amounted to 62.5% of the second cycle of 77.08%, the third cycle was 90.63%. While the mathematics learning outcomes of cyclical students 1 averaged 65, cycle 2 averaged 75, and cycle 3 averaged 80.Keywords: Activities, Learning Outcomes, Bruner's TheoryÂ